The Policy of Islamic Education in Fostering the Religious Character of Studens at MAN 5 Sleman - Syaiful Kiram; Rafif Meldi (Universitas Muhammadiyah Enrekang, 2024)
This research aims to examine the policy of Islamic education in fostering the religious character of students at MAN 5 Sleman. The study uses a qualitative method, with data collection techniques including observation, interviews, and documentation. Data analysis is conducted through data condensation, data presentation, conclusion drawing, and verification. The study highlights that the Islamic education policy at MAN 5 Sleman has been successful in fostering the religious character of students through a series of structured and planned religious programs and activities. Supporting factors include collaboration between teachers and parents, clear regulations, adequate facilities and infrastructure, teacher leadership, and collective support from various parties. Challenges such as the lack of student awareness and environmental influences need to be addressed through school and parent cooperation to ensure that religious values remain ingrained in students. The results show a significant improvement in students in terms of honesty, discipline, increased worship, social care, tolerance, noble character, which will be valuable for their future. Although providing valuable insights, this study is limited by its focus on one school, the dominant qualitative approach, and data that may not be entirely representative. This study paves the way for future research to conduct comparative studies with other schools and analyze more deeply the effectiveness of Islamic education policies in different contexts.